2017
DOI: 10.1038/s41598-017-16275-8
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Restores Mfrp and Corrects Axial Eye Length

Abstract: Hyperopia (farsightedness) is a common and significant cause of visual impairment, and extreme hyperopia (nanophthalmos) is a consequence of loss-of-function MFRP mutations. MFRP deficiency causes abnormal eye growth along the visual axis and significant visual comorbidities, such as angle closure glaucoma, cystic macular edema, and exudative retinal detachment. The Mfrp rd6 /Mfrp rd6 mouse is used as a pre-clinical animal model of retinal degeneration, and we found it was also hyperopic. To test the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 31 publications
6
48
0
Order By: Relevance
“…Rather, loss of function of this gene results in white spots apparent on retinal imaging (retinitis punctata albicans) but these have different origin from the phenotype we observe, and progress to photoreceptor degeneration. It has been reported that the Mfrp knockout mice have eyes that are slightly (but not statistically significantly) smaller, by about 2% in axial length 35 . Our analysis of the human-equivalent mouse Tmem98 mutations show that that neither have statistically significant size reductions, although the H196P line is ~7% shorter It is worth noting that different strains of mice have measurably different ocular size.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Rather, loss of function of this gene results in white spots apparent on retinal imaging (retinitis punctata albicans) but these have different origin from the phenotype we observe, and progress to photoreceptor degeneration. It has been reported that the Mfrp knockout mice have eyes that are slightly (but not statistically significantly) smaller, by about 2% in axial length 35 . Our analysis of the human-equivalent mouse Tmem98 mutations show that that neither have statistically significant size reductions, although the H196P line is ~7% shorter It is worth noting that different strains of mice have measurably different ocular size.…”
Section: Discussionmentioning
confidence: 93%
“…Instead both have the same recessive phenotype of white spots on the retina, which correlate with abnormal cells below the retina that stain with macrophage markers, and progress to photoreceptor degeneration. For the Mfrp rdx mutation, atrophy of the RPE was reported 33 and for Mfrp rd6 a modest ocular axial length reduction from about 2.87 to 2.83 mm was reported although apparently not statistically significant 35 . A screen for mice with increased intraocular pressure (IOP) found a splice mutation in the Prss56 gene predicted to produce a truncated protein 8 .…”
Section: Introductionmentioning
confidence: 94%
“…The models had an RMSD of 0.41–0.66 Å for 74 Cɑ atoms. Models of the individual domains were then assembled using ab initio domain assembly in MODELLER to generate a model of the full‐length CAPN5 structure (Figure c; Velez, Tsang, Tsai, et al, ). Using this model, we were able to better visualize the location of LOF coding variants on CAPN5's domains (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…As described by Velez, et al, Eyes were enucleated from euthanized mice, by following along the limbus to create a puncture at the 12 o'clock position. 56 Each eye was then placed in a solution of 1:2x Karnovsky fixative for 24 hours. Following fixation, eyes underwent a saline wash and then dehydration to be embedded in paraffin.…”
Section: Histologymentioning
confidence: 99%